ChemInform Abstract: An Efficient Preparation of 2‐Alkyl‐oxazoles from 2‐Iodooxazoles. Issue 45 (14th October 2013) - Zhang, Xing; Liu, Jun; Liu, Yi; Du, Yuguo
Abstract An efficient method for the synthesis of 2‐alkyl substituted oxazoles (III) via alkylborane mediated Suzuki‐coupling is described.